IMPLEMENTASI KETERSEDIAAN BERAS DALAM RANGKA KETAHANAN PANGAN DI KABUPATEN BATANG - Danna, Duta Carisma; Purnaweni, Hartuti; Mustam, Mohammad (Journal of Public Policy and Management Review, 2014)
Availability of good rice is expected to maintain food security. However, riceavailability in Batang Regency decreases although the consumption of rice is always increases. When this occurs continuously, it is feared that there will be deficits that cause weak food security.Location of the research was in Badan Pelaksana Penyuluhan dan KetahananPangan Batang Regency. Selection of informants was done using a purposive sampling.To test the quality of the obtained data, technique of triangulation was employed. As the focus of study, implementation of the policy observed through results and process, based on the policy performance of observable indicators of effectiveness, efficiency, fairness, adequacy, responsiveness and accuracy. Based on theories of Edwards III, and Van Meter & Van Horn’s implementation model synthesis, acquired the factors that support and hinder the implementation of the policy, namely communications, disposition, bureaucratic structure and resources.Based on the results of this research, implementation of the policy on theavailability of rice on Batang has yet to pan out. There are still weakness in efficiency, fairness and effectiveness.The recommendations are (1) addition of equitable distribution and infrastructures; (2) equity of efforts increased production; (3) equitable socialization and counseling services; (4) monitoring during the production process; and (5) intensive socialization and counseling.